2016
DOI: 10.1111/eci.12670
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QT and myocardium recovery after primary PCI: a cMRI study

Abstract: Viable myocardium recovering after primary angioplasty in STEMI may be predicted by the presence of increased QTc values in ischaemic areas in comparison with nonischaemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This transient QTc-prolongation has been described to differ from the persistent QTc-prolongation associated with an increased risk of ventricular arrhythmia and poor outcome. 43,44 To the best of our knowledge, the phenomenon with transient long QTc as a marker for stunning has not been demonstrated in non-anterior STEMI specifically. Additional studies, ideally with serial assessment of ECGs, are needed to better understand the dynamic nature of QTc prolongation in anterior vs. non-anterior STEMI.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This transient QTc-prolongation has been described to differ from the persistent QTc-prolongation associated with an increased risk of ventricular arrhythmia and poor outcome. 43,44 To the best of our knowledge, the phenomenon with transient long QTc as a marker for stunning has not been demonstrated in non-anterior STEMI specifically. Additional studies, ideally with serial assessment of ECGs, are needed to better understand the dynamic nature of QTc prolongation in anterior vs. non-anterior STEMI.…”
Section: Discussionmentioning
confidence: 96%
“…The lack of an association between QTc and LTVA or death in anterior STEMI is also consistent with previous data, because early and transient prolongation of QTc in anterior STEMI have been associated with stunned viable myocardium with increased potential for recovering cardiac function, smaller infarct size, and higher LVEF. This transient QTc‐prolongation has been described to differ from the persistent QTc‐prolongation associated with an increased risk of ventricular arrhythmia and poor outcome 43,44 . To the best of our knowledge, the phenomenon with transient long QTc as a marker for stunning has not been demonstrated in non‐anterior STEMI specifically.…”
Section: Discussionmentioning
confidence: 97%
“…A prolonged QT interval is also described after myocardial infarction and might be related to viable myocardium or systemic inflammation 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have described this pattern of dynamic QT prolongation/T wave inversion as equal to Wellen’s ECG pattern [26] , which previously has been viewed as unfavorable because of the link to sub-occlusive LAD stenosis [27] . However, later studies have suggested transient QT prolongation/T wave inversion as a marker of stunned viable myocardium in AMI patients recovering after reperfusion [28] , [29] . Wellen’s ECG pattern per se has been attributed to myocardial edema [26] , and CMR studies have shown myocardial edema in both STEMI and TTS.…”
Section: Discussionmentioning
confidence: 99%